Chlorophyl-a Distribution and Sea Surface Temprature Using Modis Aqua Image Data in Bone Bay Waters - Dwi Rosalina; Lalu Penta Febri Suryadi; Ani Leilani; Suci Puspita Sari; Mustafa Mustafa; Yakub Suleman; Khairul Jamil; Agus Surachmat; Maharani Maharani (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2024)
ABSTRACTOne of the parameters determining productivity in the sea is chlorophyll-a. The fertility level of chlorophyll-a is closely related to the concentration of chlorophyll-a. The higher the concentration of chlorophyll-a, the higher the water fertility level, conversely, if chlorophyll-a is low, the water fertility level will also be low. One factor influencing growth rate and chlorophyll-a production is temperature. This research aimed to determine the distribution of chlorophyll-a and sea surface temperature based on season in 2022 in the waters of Bone Bay using quantitative descriptive method and geographic information analysis (GIS) procedure in the form of analysis of Aqua MODIS remote sensing image data. The research results showed that the highest distribution of chlorophyll-a occurred in the east season with a concentration of 0.06-2.04 mg/m³, while the lowest distribution of chlorophyll-a occurred in the west season with a concentration of 0.07-1.76 mg/m³. Meanwhile, the highest intensity sea surface temperature distribution occurred in the west season, which was 28.76-37.09 °C and the lowest sea surface temperature distribution fell in the east season, which was 27.13-33.62 °C. Spatial temperature variability and sea surface chlorophyll-a can be used as information about potential areas for fishing grounds.Key words: chlorophyll-a distribution, sea surface temperature, Bone Bay, Aqua MODIS